2015
DOI: 10.14235/bs.2015.392
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Respiratory Parameters of Physically Disabled and Healthy Children

Abstract: Objective: The aim of this study was to compare the respiratory parameters of physically disabled and healthy children. Methods:The study included 25 children. Of these children, 13 were physically disabled and 12 were healthy children. The BTL-08 spirometry device was used for measuring the respiratory values of the children. The gross motor function classification system (GMFCS) and manual ability classification system (MACS) levels were determined.Results: A statistically significant difference was found be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The poor coordination pattern that accompanies the respiratory muscles causes decreases in cardiopulmonary capacity and respiratory volume in children with CP who have respiratory problems [11]. In the study in which the respiratory function of children with diparetic and spastic hemiparetic CP was compared with healthy children, it was shown that there was a decrease in the respiratory capacity of children with CP and a statistical significance in FEV1, FVC, PEF values between the groups [12]. In the present study, we investigated and compare trunk control and respiratory functions of children with CP who we classified according to their functional levels.…”
Section: Introductionmentioning
confidence: 99%
“…The poor coordination pattern that accompanies the respiratory muscles causes decreases in cardiopulmonary capacity and respiratory volume in children with CP who have respiratory problems [11]. In the study in which the respiratory function of children with diparetic and spastic hemiparetic CP was compared with healthy children, it was shown that there was a decrease in the respiratory capacity of children with CP and a statistical significance in FEV1, FVC, PEF values between the groups [12]. In the present study, we investigated and compare trunk control and respiratory functions of children with CP who we classified according to their functional levels.…”
Section: Introductionmentioning
confidence: 99%